2014
DOI: 10.1016/j.jplph.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological assessment of water stress in fruit-bearing woody plants

Abstract: Development and evaluation of a real-time plant water stress sensor, based on the electrophysiological behavior of fruit-bearing woody plants is presented. Continuous electric potentials are measured in tree trunks for different irrigation schedules, inducing variable water stress conditions; results are discussed in relation to soil water content and micro-atmospheric evaporative demand, determined continuously by conventional sensors, correlating this information with tree electric potential measurements. Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 39 publications
1
28
0
1
Order By: Relevance
“…A different system was described and tested in cucumber plants under greenhouse conditions by Wang et al [200]. Recently, Ríos-Rojas et al [201,202] developed a system for remote, real-time recording of plant electrical potential in the field and data transmission via Internet. The authors concluded that their system could be used to monitor water stress and, combined with soil moisture and potential evapotranspiration sensors, to schedule irrigation.…”
Section: Electrical Potentialmentioning
confidence: 99%
“…A different system was described and tested in cucumber plants under greenhouse conditions by Wang et al [200]. Recently, Ríos-Rojas et al [201,202] developed a system for remote, real-time recording of plant electrical potential in the field and data transmission via Internet. The authors concluded that their system could be used to monitor water stress and, combined with soil moisture and potential evapotranspiration sensors, to schedule irrigation.…”
Section: Electrical Potentialmentioning
confidence: 99%
“…39 In Figure 1C and 2C, the climatic effect on EP in well-watered plants (red line) is observed with successive changes in the slope of the daily maximum EP values, in coordination with changes in air temperature and solar radiation ( Fig. 1A and B; 2A and B).…”
Section: Resultsmentioning
confidence: 83%
“…According to reports by 3,4,26,39 plants respond electrically to stimuli generated in its micro-environment, and strong evidence indicates that soil water availability directly influences the electrical response of plants. Our results sustain these early reports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative effect of water stress on germination was reported by many authors for severals plants species (Amara et al, 2013;Rios-Rojas et al, 2014;Zhou et al, 2015). For this species, water soil has more complicated effects on germination than temperature because water is the initial factor for seed imbibitions and germination; it is directly and indirectly involved in subsequent germination metabolic stages (Cavalcante and de Perez, 1995) in particularly under arid and semi arid environment.…”
Section: Discussionmentioning
confidence: 93%